Design of Mobile Gateway for Implementation of Smart Work System - Sang-Young Oh; Bong-Hyun Kim (Modelling and Simulation in Engineering)
In the development of new technologies based on mobile system, there is a growing interest as a fundamental technology. In particular, in order to realize a mobile office and mobile phones, conferencing remote document is a technique that can realize smart network services solutions with enhanced real-time communication, real-time information sharing, and collaboration. Therefore, in this paper, the design meets the diverse needs of customers and the smart work platform mobile-based fast and conveniently it is trying to develop. For this reason, I have developed a mobile gateway that is based on the communication server construction OPEN API development, management of mobile ID, protocol design, and design of SSL/TLS security tunnel. Also, we developed a smart work platform that you apply this, you are trying to provide information systems environment of mobile company.